Artificial intelligence - Open AI ChatGPT Challenges of digital reality in education - Zakariashvili, Mariam (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
The development of digital technologies, particularly in the context of Artificial Intelligence (AI-Art Intelligence), is creating a new dynamic within the field of education. Digital innovation promises a more effective, personalized, and interactive learning process but also presents significant challenges that must be addressed to shape future educational systems. This ensures that the learning process becomes not only innovative but also stable and sustainable. To this end, the paper discusses ChatGPT, one of the most widely used and powerful models developed by OpenAI, outlining its purpose and fundamental operating principles. It explores the technological aspects of utilizing the ChatGPT platform within higher education through a teaching/research project example titled "ChatGPT for Education Transformation". The paper provides a detailed account of the project model's implementation process. It examines and analyzes the primary challenges and achievements of ChatGPT in transforming student learning and teaching practices.